ANÁLISE ESTRATÉGICA PARA IMPLANTAÇÃO DE EMPRESAS DE PEQUENO PORTE: CERVEJARIAS ARTESANAIS - Joanir Luís Kalnin; Nelson Casarotto Filho; João Ernesto E. Castro (Revista Produção Online, 2002)
In the late 1980’s, following the success in the US and Europe, a new market segment with a high capital investment/return ratio was started in Brazil. It is called Craft Brewing and it is characterized by small breweries producing alternative beer. The author of this paper, through the analysis of the achievements and failures of this business in Brazil, proposes a strategy definition model for the segment, aiming at increasing the chances of success of the small entrepreneurs interested in investing in this kind of business.